Shedding light on the unseen: how live imaging of translation could unlock new insights in developmental biology - Dufourt, Jeremy; Bellec, Maelle (Comptes Rendus Biologies)
Recent advances in live imaging technologies have refined our understanding of protein synthesis in living cells. Among the various approaches to live imaging of translation, this perspective highlights the use of antibody-based nascent peptide detection, a method that enables visualization of single-molecule translation in vivo. We examine how these advances improve our understanding of biological processes, particularly in developing organisms. In addition, we discuss technological advances in this field and suggest further improvements. Finally, we review some examples of how this method could lead to future scientific breakthroughs in the study of translation and its regulation in whole organisms.